Constructive Effects of Alkyl Chains: A Strategy to Design Simple and Non‐Spiro Hole Transporting Materials for High‐Efficiency Mixed‐Ion Perovskite Solar Cells. Issue 13 (4th May 2016) - Zhang, Jinbao; Xu, Bo; Johansson, Malin B.; Hadadian, Mahboubeh; Correa Baena, Juan Pablo; Liu, Peng; Hua, Yong; Vlachopoulos, Nick; Johansson, Erik M. J.; Boschloo, Gerrit; Sun, Licheng; Hagfeldt, Anders
Abstract : A series of simple alkylated triphenylamine molecules are designed and synthesized as hole transporting materials (HTMs) for perovskite solar cells. The effects of the alkyl chains on the photovoltaic performance are for the first time systematically investigated. A high efficiency of 17.33% is achieved by combining HTM X21 and the mixed‐ion perovskites.